Reduction of Pulmonary Hypertension After Transition to Sacubitril/Valsartan in Patients With Heart Failure With Preserved Ejection Fraction - Burgdorf, Christof; Brockmöller, Janine; Strampe, Henrieke; Januszewski, Monika; Remppis, Bjoern Andrew (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Although the PARAGON-HF trial failed to reach its primary endpoint, subgroups of patients with heart failure with preserved ejection fraction (HFpEF) still appear to benefit from Sacubitril/Valsartan therapy. As HFpEF patients with pulmonary hypertension display a specifically high mortality and morbidity, we evaluated the effect of Sacubitril/Valsartan in this subgroup of HFpEF patients. Methods: In this retrospective case-series of 18 patients with HFpEF and pulmonary hypertension, right heart catheterisation (RHC) for determination of invasive pulmonary pressure were performed at baseline (pre-Sacubitril/Valsartan) and 99 (71 - 156) days after transition from angiotensin-converting enzyme inhibitors and angiotensin receptor blockers to Sacubitril/Valsartan (post-Sacubitril/Valsartan). Results are given as median and interquartile range. Results: After conversion to Sacubitril/Valsartan, RHC showed significantly reduced pulmonary artery pressure (PAP) and mean pulmonary capillary wedge pressure (PCWP) compared to pre-Sacubitril/Valsartan (PAP systolic/diastolic/mean 44 [38 - 55]/15 [11 - 20]/27 [23 - 33] mm Hg versus 51 [41 - 82]/22 [13 - 29]/33 [28 - 52] mm Hg, p < 0.05 and p < 0.01, respectively; PCWP 16 [12 - 20] mm Hg versus 22 [15 - 27] mm Hg, p < 0.05). Median Sacubitril/Valsartan dosage was 24/26 mg BID (24/26 BID - 49/51 mg BID). Clinically, New York Heart Association functional class improved in 12 of the 18 patients (p < 0.01) after conversion to Sacubitril/Valsartan. Echocardiographic parameters of left ventricular function and cardiovascular co-medication did not differ markedly between pre- and post- Sacubitril/Valsartan. Conclusion: Sacubitril/Valsartan therapy is associated with an improvement of pulmonary hypertension in HFpEF patients.